Understanding the Broad-line Region of Active Galactic Nuclei with Photoionization. I. The Moderate-accretion Regime - Qiaoya Wu; Yue Shen; Hengxiao Guo; Scott F. Anderson; W. N. Brandt; Catherine J. Grier; Patrick B. Hall; Luis C. Ho; Yasaman Homayouni; Keith Horne; Jennifer I-Hsiu Li; Donald P. Schneider (The Astrophysical Journal)
Over three decades of reverberation mapping (RM) studies on local broad-line active galactic nuclei (AGNs) have measured reliable black hole (BH) masses for >100 AGNs. These RM measurements reveal a significant correlation between the Balmer broad-line region (BLR) size and AGN optical luminosity (the R – L relation). Recent RM studies for AGN samples with more diverse BH parameters (e.g., mass and Eddington ratio) reveal a substantial intrinsic dispersion around the average R – L relation, suggesting that variations in the broadband spectrum, driven by accretion parameters and other factors such as the cloud distribution and inclination, significantly influence the measured R – L relation. Here we perform a detailed photoionization investigation of expected broad-line properties as functions of accretion parameters using AGN continuum models from qsosed . We compare theoretical predictions with observations of a sample of 67 z ≲ 0.5 reverberation-mapped AGNs with rest-frame optical and UV spectra in the moderate-accretion regime (Eddington ratio λ _Edd ≡ L / L _Edd < 0.5). The UV/optical line strengths and their dependences on accretion parameters are reasonably well reproduced by the locally optimally emitting cloud photoionization models. We provide quantitative recipes using optical/UV line flux ratios to infer the unobservable ionizing continuum. Additionally, photoionization models with universal values of ionization parameter ( $log\,U_{{\rm{H}}}=-2$ ) and hydrogen density ( $log\,n({\rm{H}})=12$ ) can qualitatively reproduce the observed global R – L relation for the current RM AGN sample. However, such models fail to reproduce the observed decrease in BLR size with increasing L / L _Edd at fixed optical luminosity, implying that gas density or BLR structure may systematically change with accretion rate.